Satisfaction towards Banking Profession: A Comparative Study on Male and Female Executives - Uddin, Mohd Kamal; Kabir, Mohammad Jonaed (IIUC Studies, 2016)
Banking sector in Bangladesh is recruiting women more in number than ever before. Women are now viewed by planners and policy makers as equal partners in the process of development and great contributors to state economy. Banks, as development catalysts, need to evaluate both the male and female employees, in a timely manner to enhance their effort to work. This paper attempts to evaluate job satisfaction of bank officers considering sex differences to determine a fruitful comparison. The research work was conducted through JDI administered questionnaire on a sample of 210 employees from six banks (Two public and four private banks). A popular measure of job satisfaction - the Job Descriptive Index (JDI) - measure satisfaction in terms of five aspects of a persons job: pay, promotion, supervision, the work itself and co-workers (Hellriegel and Woodman, 1995). As the two gender groups were not normally distributed, a Mann-Whitney U test was applied to test relationship between gender and job satisfaction with each facet. The findings of the study show that higher satisfaction among females for three of the five job facets while male officers dominate the rest two factors. The present study attempts to enrich the existing knowledge base in the area of job satisfaction in banking sector adding a new dimension of HRM-issues. IIUC Studies Vol.12 December 2015: 127-138